Profil Kemampuan Pemahaman Matematis Siswa SMK Swasta Otomindo Jakarta pada Materi Sistem Persamaan Linear Dua Variabel - Cindi Sinaga; Bitman Manullang; Santri Chintia Purba (Brillo Journal, 2022)
Lesson plans are more focused on how to achieve goals and indicators. However, student ability profile has not become the main basic standard. Therefore, this research aims to describe the profile of students' mathematical understanding abilities. This research is a quantitative descriptive conducted on XI grade Otomindo’s vocational students in Jakarta. Data obtained from student achievement on the understanding ability test. Students' understanding is profiled according to the results of data analysis on their level and abilities based on achievement in mechanical, inductive, rational and intuitive indicators. The results of the study concluded that the profile of students' mathematical understanding abilities was dominated by inductive understanding abilities. It is because students are better able to apply formulas or concepts to simple or similar problems, but it is difficult to the rational and intuitive indicators. Students' mathematical understanding ability is included in the low category on two indicators, that is rational in terms of describing the truth of formulas and theorems, and intuitive in term of estimating the truth before analyzing further. While in the medium category, it is on mechanical indicators in terms of remembering and applying formulas routinely and calculating simply.